Challenges in preparing the dietetics workforce of the future: An exploration of dietetics educators' experiences. Issue 4 (13th June 2018) - Morgan, Kate; Reidlinger, Dianne P.; Sargeant, Sally; Crane, Linda; Campbell, Katrina L.
Abstract : Aim: Dietetics educators represent a small but influential workforce group that has experienced significant change in recent years. The workforce development challenges faced by this group have been largely unexplored. The present study aimed to explore the experiences of, and challenges faced by, academic dietetics educators in preparing dietitians for the workforce. Methods: The approach taken in the present study was informed by qualitative description. Fifteen dietetics educators employed by 13 universities across Australia were purposively sampled. In‐depth, semi‐structured interviews conducted via telephone (n = 12) or face‐to‐face (n = 3) were digitally recorded then transcribed verbatim. Data were managed with NVivo and inductively analysed using open coding. Codes were condensed into themes through an iterative process involving multiple researchers. Results: The overarching theme of 'aiming for a moving target' was underpinned by the themes of: (i) striving for betterment; (ii) bridging dissonance and (iii) distressing impossibilities. Interviewees described how they were driven to enhance the preparation of dietitians but acknowledged disparity between what graduates are being prepared for and what they need to be prepared for. Heightened expectations of others, professional constraints and a lack of collegiality among the profession were among the challenges that manifested in a sense of frustration, concern and isolation. Conclusions: Dietetics educators are motivated to shape and enhance the future profession. However, they face numerous challenges in their efforts to prepare graduates who are well‐equipped for increasingly diverse dietetics practice. Strong leadership, academic collaboration and greater engagement of the broader workforce are required for the benefit of the entire profession.